Organisational health and performance: an empirical assessment of smallholder producer organisations in Africa - Wouterse, Fleur; Francesconi, Gian N. (Wageningen University & Research, 2016)
We use recent data from 253 smallholder producer organisations (SPOs) in Ethiopia, Malawi and Senegal, factor and regression analysis to define organisational health, understand its determinants and relate health to performance. We find that latent health evolves according to a life cycle and that start up incentives and design rules are important determinants of an organisation’s progression through this life cycle. Health, in turn, is found to explain SPO performance measured in terms of profits. Healthier and more profitable SPOs are those with an economic justification at establishment, those initially pursuing defensive objectives and those SPOs that have put in place a strategy for capital formation. More educated presidents contribute to the health of an SPO but it is also shown that when the president of the SPO is female, profits are lower while the organisation is not healthier.